2009
DOI: 10.1258/jtt.2008.080706
|View full text |Cite
|
Sign up to set email alerts
|

Videophones for intensive case management of psychiatric outpatients

Abstract: When visiting patients with serious mental illness at their homes, case managers carried a portable videophone. This was used to access the hospital clinical team via the home telephone line, when an acute clinical need arose in addressing questions related to medication management and treatment planning; travel was therefore avoided. In an acceptability study lasting 12 months, 24 patients received the supplemental videophone mental health service and 19 of them completed a satisfaction survey. Only one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The only study published prior to 2007 involved a telehealth digital intervention. 45 Most of the studies used mixed methods, 28,29,31,32,34,35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] four used quantitative methods 30,33,36,51 and two studies used qualitative methodology. 52,53 The majority of the studies were feasibility and acceptability trials (42%), 29, 35, 36, 38, 40, 42-44, 50, 53 eight were designed to look specifically at implementation (31%), 28, 30, 32, 45-47, 49, 52 five were pilot studies (19%), 31,39,…”
Section: Description Of the Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The only study published prior to 2007 involved a telehealth digital intervention. 45 Most of the studies used mixed methods, 28,29,31,32,34,35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] four used quantitative methods 30,33,36,51 and two studies used qualitative methodology. 52,53 The majority of the studies were feasibility and acceptability trials (42%), 29, 35, 36, 38, 40, 42-44, 50, 53 eight were designed to look specifically at implementation (31%), 28, 30, 32, 45-47, 49, 52 five were pilot studies (19%), 31,39,…”
Section: Description Of the Studies Includedmentioning
confidence: 99%
“…44,53 Staff spoke of a telehealth intervention being particularly suited to supporting those who had a need or incentive to stay at home. 50 Digital interventions were also reported to aid communication and help build relationships between users and their medical team. 32,41,44,48 In a shared decision-making intervention for psychotropic medication, it was reported that users were able to disclose information that they felt uncomfortable or unable to tell a clinician directly, for example, about drug and alcohol relapse, pregnancy plans, wanting "hip-hop abs", and general concerns about using medication.…”
Section: Relative Advantagementioning
confidence: 99%
“…Four reviews of literature concerning patient satisfaction with telemedicine services show that satisfaction is high, generally over 80% and often reported at 100%. [7][8][9][10] Four studies, two with individuals who experienced a stroke, 11,12 one with inpatients in a gero-psychiatric setting, 13 and one with psychiatric outpatients, 14 have shown high satisfaction with videoconferencing, 11,13 virtual reality therapy, 12 and videophone usage. 14 Another study that provided patients with a range of problems (e.g., weight concerns, self-esteem issues, personality disorders) with five free sessions of cognitive-behavioral therapy via videoconferencing between separate hospital rooms showed high patient and therapist satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Among telehealth approaches for treating SMI, a mobile phone-based program that involved weekly completion of a 10-item early warning sign questionnaire, and online alerts sent to the treating psychiatrist if scores exceeded a given threshold, was shown to reduce hospitalizations in people with schizophrenia (Spaniel et al, 2008). Other telehealth interventions targeting this vulnerable group include video-conferencing (Nieves et al, 2009), informational websites (van der Krieke et al, 2012), telephone-based therapy (Cook et al, 2008), and smartphone-based interventions in early development that consist of frequent real-time symptom self-assessment and monitoring (Ben-Zeev et al, 2013). …”
Section: Introductionmentioning
confidence: 99%